Challenges and Opportunities in the Implementation of Early Literacy Intervention Among Kindergarten Teachers - Wenecyl F. Manuel; Wenie L. Nahial (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Addressing reading problems at an early stage is recommended to reduce the adverse effects on the pupils. This study aimed to identify the challenges encountered and opportunities experienced during the implementation of early literacy interventions in kindergarten. In this regard, 41 kindergarten teachers responded positively in providing the needed data. A quantitative descriptive research design was employed, supplemented with a survey questionnaire as the primary data collection tool, and casual interviews for follow-up. Research protocols of Dep-Ed-Bukidnon were observed at all times. Appropriate statistical tools were used to produce reliable results. Analysis showed that the majority of respondents were young adults with units in master’s degree programs in education, and they came from small schools. The highest counts of respondents served for 6 to 10 years and attended 6 or more training sessions related to early literacy intervention, initiated and sponsored by the Division Office. The respondents had consistently encountered challenges and experienced opportunities during the implementation of early literacy interventions. A moderate, positive, and significant relationship was found between the challenges encountered and the opportunities experienced during the implementation of early literacy intervention. There was no significant difference in the extent of challenges encountered among the respondents when grouped by age, years in teaching, highest educational attainment, and number of trainings attended. However, there was a significant difference in the challenges encountered when grouped by school size. Respondents from small and medium-sized schools encountered more challenges than those from large schools.